Penyiangan Koleksi Bahan Pustaka di Kantor Perpustakaan dan Dkumentasi Kota Padang - Betriati, Betriati; Marlini, Marlini (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2015)
This paper focuses on weeding the collection of library materials in office archives, libraries and documentation desert city. This study aimed to describe: (1) a way of weeding of library materials in the Archives, Library and Documentation of Padang; (2) the obstacles encountered in the process of weeding of library materials in the Archives, Library and Documentation of Padang; (3) and efforts should be made to overcome the obstacles weeding of library materials in the Archives, and Documentation Perpustaaan Padang. Data were collected through observation, interview and literature study. Analyzing data descriptively.By analyzing the data, it was concluded matters as follows: First, the process of weeding activities of library materials in the Archives, Perpusakaan and Documentation of Padang has not done effectively, these activities are still limited to the separation of collection / library materials. secondly, the constraints faced in weeding activities in the library at the Archives, Library and Documentation city of Padang is the absence of a written policy for doing weeding and no follow-up after the weeding. Third, efforts yag can be done at the Archives, and Documentation Perpstakaan city of Padang is giving himbawan to do weeding, giving solicitation/ procedures for weeding, and add more collections.Keywords: Weeding, Library, Material